Perlindungan Hukum Pelanggan Aset Kripto Transaksi Perdagangan Berjangka Komoditi Indonesia - Ika Atikah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This study explains the importance of regulating government legal protection in the form of legal regulations for crypto asset customers in commodity futures trading activities. The ease of digital transactions in the form of crypto investments that have high risk requires unusual legal arrangements so that the urgency of institutions such as CoFTRA have a hand in the commodity futures trading traffic. The results of the research provide an answer that specifically it is not regulated in the form of a separate law but is regulated explicitly by CoFTRA in the form of a CoFTRA, which regularly updates regulatory policies every year, trading activities for commodity futures crypto assets No.8/2021 and the legitimacy of crypto transactions strengthened by the stipulation of PMK No.68/2022 PPN and PPH. Through institutions that have the authority to regulate and limit crypto transactions, the government has provided legal and registered balanced protection not only to crypto asset traders but also to crypto asset customers. The Ministry of Trade of the Republic of Indonesia, through CoFTRA, seeks to regulate the transaction mechanism of crypto asset trading activities in such a way that all parties involved in the digital transaction can comply with and apply it, including crypto customers, seeks to provide education in the form of socialization movements to the public as potential crypto customers by first studying investment high risk to minimize losses that occur in the future.Keywords: Protection; Customer; Crypto Asset; Commodity Futures Trading Abstrak Penelitian ini menjelaskan penting mengatur proteksi hukum pemerintah dalam bentuk peraturan hukum kepada pelanggan aset kripto dalam kegiatan dagang berjangka komoditi. Kemudahan transaksi digital dalam bentuk investasi kripto yang memiliki risiko tinggi memerlukan pengaturan hukum yang tidak biasa sehingga urgensitas lembaga seperti Bappebti memiliki andil dalam lalu-lintas perdagangan berjangka komoditi tersebut. Hasil riset memberikan jawaban bahwa secara khusus tidak diatur dalam bentuk Undang-Undang secara tersendiri melainkan secara spesifik diatur oleh Bappebti dalam bentuk Perbappebti yang secara berkala kebijakan regulasi selalu diperbaharui setiap tahunnya kegiatan transaksi dagang berjangka komoditi aset kripto No.8/2021 dan legitimasi transaksi kripto diperkuat dengan ditetapkan PMK No.68/2022 PPN dan PPH. Pemerintah melalui lembaga yang memiliki kewenangan mengatur dan membatasi transaksi kegiatan kripto telah memberikan proteksi yang berimbang legal dan terdaftar tidak hanya kepada pedagang aset kripto saja namun juga kepada pelanggan aset kripto. Kemendag RI melalui Bappebti berupaya mengatur mekanisme transaksi kegiatan perdagangan aset kripto dengan sedemikian baik agar dapat dipatuhi dan diterapkan oleh semua pihak yang terlibat dalam transaksi digital tersebut termasuk pelanggan kripto, berupaya memberikan edukasi berupa gerakan sosialisasi kepada masyarakat sebagai calon pelanggan kripto dengan mempelajari terlebih dahulu investasi berisiko tinggi tersebut guna meminimalisir kerugian yang terjadi kemudian hari.Kata Kunci: Perlindungan; Pelanggan; Aset Kripto; Berjangka Komoditi